Evaluation of Collaborative Learning in the Development of Technology-Based Entrepreneurial Skills at Muhammadiyah Prambanan Vocational High School - Sofyan, Esfan; Budiastuti, Pramudita (Jurnal Edukasi Elektro, 2024)
The purpose of this research is to promote entrepreneurship education in universities, develop students' entrepreneurial soft skills, and create opportunities for students to produce creative works and innovative products. This study is evaluation research using a descriptive quantitative method. The research methodology follows the Context, Input, Process, and Product (CIPP) model. Context refers to the collaboration in learning and the standards for implementing entrepreneurship education. Input involves entrepreneurship program planning and program participants. Process refers to the execution of the entrepreneurship education program and workshops. Product refers to the effectiveness of the program's implementation and program evaluation. The sample of this research consists of 20 teachers and 20 students. The data analysis technique involves the use of descriptive statistical methods. The evaluation of context is found to be relevant, with an average score of 63.67, a mean of 3.35, and a TCR of 67.62%. The evaluation of input is highly relevant, with an average score of 9.11, a mean of 4.56, and a TCR of 91.11%. The evaluation of process is relevant, with an average post-test score of 73.11, a mean of 3.85, and a TCR of 76.96%. The evaluation of product is relevant, with an average score of 64.57, a mean of 3.4, and a TCR of 67.97%. The implication of this research is the existence of entrepreneurship education in universities, the development of students' entrepreneurial soft skills, and students producing creative works and innovative products.